Special Education and ICTs - Drigas, Athanasios; Ioannidou, Rodi Eleni (International Journal of Emerging Technologies in Learning (iJET), 2013)
Recent development in special education includes the use of Information and Communication Technologies (ICTs) to assist students during their lifetime. ICT is now also recognized as a tool which ensures access to knowledge and learning resources. In this paper we present an overview of the most representative studies of the last decade (2001-2010) which deal with the two important issues in the field of special education, diagnosis and intervention. One important advantage of these tools is that they can be employed by teachers and parents as well, to adapt education to the needs and abilities of pupils. The studies chosen will be classified according to the areas of needs they serve.